2019
DOI: 10.21276/ijcmr.2019.6.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Clonidine Vs Dexmedetomidine for Hemodynamic Stability and Postoperative Analgesia during Laproscopic Surgery

Abstract: Introduction: Alpha-2 (α2) adrenergic receptor agonists, clonidine and dexmedetomidine, are widely used as adjuvants during anesthesia for analgesic, sedative, sympatholytic, and cardiovascular stabilizing effects. The aim of this study was to differentiate the effectiveness of intravenously administered clonidine and dexmedetomidine for hemodynamic stability and postoperative analgesia during laparoscopic surgery. Materials and methods: This was a randomised, double blind and prospective study in which Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Group I patients received 0.9% normal saline (placebo), group II patients received 0.5 µg/kg of dexmedetomidine and group III patients received 3 µg/kg of or clonidine. Pooja et al, [10] in their study group 1 received 2 µg/kg of clonidine and group 2 patients received 1 µg/kg of dexmedetomidine Results showed that the mean scores of SBP were higher in group 1 among both the groups over the periods. The mean scores of DBP in both groups was similar over the periods with slightly being higher in Group 1 especially after 30 min to till end as compared to Group 2.…”
Section: Discussionmentioning
confidence: 91%
“…Group I patients received 0.9% normal saline (placebo), group II patients received 0.5 µg/kg of dexmedetomidine and group III patients received 3 µg/kg of or clonidine. Pooja et al, [10] in their study group 1 received 2 µg/kg of clonidine and group 2 patients received 1 µg/kg of dexmedetomidine Results showed that the mean scores of SBP were higher in group 1 among both the groups over the periods. The mean scores of DBP in both groups was similar over the periods with slightly being higher in Group 1 especially after 30 min to till end as compared to Group 2.…”
Section: Discussionmentioning
confidence: 91%
“…Dexmedetomidine attenuates systolic blood pressure changes during pneumoperitoneum more effectively than clonidine when administered intravenously before induction. 12 Basar et al, 13 used 0.5 mcg/kg dexmedetomidine as a single pre-operative dose and found blunting of hemodynamic responses. Bhattacharjee et al, 14 infused 0.2 mcg/kg/h dexmedetomidine and found significantly less MAP and heart rate throughout the period of pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…The attenuation of hemodynamic responses was better controlled with dexmedetomidine than clonidine 10. Other studies11,12 also report about better control of heart rate in patients receiving dexmedetomidine compared with clonidine during intubation and pneumoperitoneum.…”
mentioning
confidence: 84%